On determinants and permanents of k-Tridiagonal toeplitz matrices - Mustafa, AŞci,; Dursun, TAŞci,; Moawwad, E.L.-Mikkawy, (Utilitas Mathematica, 2012)
In this paper we introduce k-tridiagonal Toeplitz matrices and give algorithms for determinants and permanents of these matrices. We give illustrative examples for these algorithms. In the last section we give examples of matrices whose determinants are powers of generalized Fibonacci numbers. These algorithms can be implemented in all Computer Algebra Systems (CAS).